The Food Security Management Based on the Perspective of Cakti Food Barn Theory in East Java, Indonesia - Setyanto, Agustinus Budi (International Research & Development for Human Beings (IRDH), 2024)
The era of the COVID-19 pandemic also had an impact on food availability, such as the decline in agricultural commodities and the crises of food. East Java is a region that is vulnerable and resistant to food availability. This research aims to depict food security management based on the perspective of Cakti Food Barn Theory in East Java, Indonesia. This method using This research uses a comparative literature review coming from various sources with descriptive analytic data types. The result shows that the requirements of the Cakti food barn consist of the availability of large buildings, a management information system to detect food availability, special forces from military and police elements, availability of agricultural experts and the application of gotong royong (good collaboration). The Cakti Food Barn Theory would apply to the villages. It consists of 10 barns such as Food Barn, Water Barn, Energy Barn, Fisheries and Cattle Barn, Health Barn, Religion and Beliefs Barn, Education barn, Economic and employment barn, Administration, security, and law barn, and also Investment barn. Furthermore, the key of the Cakti Food Barn is collaboration from various stakeholders.